Electrochemical study of the surface metal matrix composite developed on AA 2024-T351 by the friction stir process. (17th November 2019) - Acuña, R.; Abreu, C. M.; Cristóbal, M. J.; Cabeza, M.; Nóvoa, X. R.
ABSTRACT: This work is focused on the evaluation of the corrosion behaviour of an AA2024-T351/SiC surface composite produced by friction stir processing (FSP). The surfaces composite show a quite homogenous distribution of the SiC particles in the stir zone, together with a significant grain size reduction as Electron Backscatter Diffraction analysis confirms. The corrosion behaviour was evaluated in 3.5 wt-% NaCl solution using electrochemical techniques. The complete study shows that all processed samples have similar corrosion resistance at the stirred region and differ from the base material behaviour. The results indicate that the galvanic coupling metal matrix–SiC particles are less active than the galvanic coupling metal matrix–Cu-rich second phases. Although the initial corrosion resistance of the base aluminium alloy is the worst of all systems studied, for long immersion times the development of corrosion through grain boundaries was found to progressdeeper in the 2024Al/SiC surface produced by FSP.